Study on Effect of Dilatational Wave Applied in Osteoarthritis Rehabilitation Treatment - Jie LIN; Guangwen WU (康复学报)
In recent years, with the development of rehabilitation medicine and physical therapy, dilatational wave is widely used in osteoarthritis rehabilitation treatment. In this paper, the physics and biology features of dilatational wave and its application in osteoarthritis rehabilitation treatment were summarized, and the deficiency of current research and the future research direction were also put forward, so as to provide guidance on the application of dilatational wave in osteoarthritis rehabilitation treatment.